USING THE ECOLOGICAL PRINCIPLE IN THE ARRANGEMENT OF BREEDING PROCESS TO DEVELOP SPRING TRITICALE CULTIVARS - A. M. Tyslenko; S. E. Skatova (Труды по прикладной ботанике, генетике и селекции, 2018)
Since 2003, a large-scale study of spring triticale source material of different ecogeographic origin was carried out to launch the breeding work with this crop in the non-black-soil zone of Russia. Accessions and populations from the collections and nurseries of CIMMYT (Mexico), Vavilov Institute, Krasnodar Agricultural Research Institute and Science and Production Centre for Agriculture (Belarus) were evaluated. The breeding process was arranged according to the ecological principle: identification of the required sources and the study of hybrid populations and the developed breeding lines were done concurrently at several sites under different environmental conditions. As a result, four cultivars of spring triticale have been included in the State Register.